Inhibition of pilocarpine-induced salivation in rats by central noradrenaline - Moreira, T. D.; Takakura, ACT; De Luca, L. A.; Renzi, Antonio [UNESP]; Menani, José Vanderlei [UNESP] (Elsevier B.V., 2002)
Peripheral treatment with cholinergic or adrenergic agonists results in salivation and the possibility of synergy between cholinergic and adrenergic efferent mechanisms in the control of salivation has been proposed. Central injections of the cholinergic agonist pilocarpine also induce salivation, while the effects of central injections of noradrenaline (norepinephrine) are not known. Here (a) the effects of intracerebroventricular (icv) injection of noradrenaline on the salivation induced by icv or intraperitoneal (i.p.) injection of pilocarpine and (b) the receptors involved in the effects of central noradrenaline on pilocarpine-induced salivation were investigated. Male Holtzman rats with a stainless-steel guide cannula implanted into the lateral ventricle were used. Rats were anaesthetized with tribromoethanol (200 mg/kg body weight) and saliva was collected on small, preweighed cotton balls inserted into the animal's mouth. Noradrenaline (40, 80 and 160 nmol/l mul) injected icv reduced the salivary secretion induced by pilocarpine (0.5 mumol/l mul) injected icv. Noradrenaline (80 and 160 nmol/l mul) injected icv also reduced the salivation induced by pilocarpine (4 mumol/kg) injected i.p. Previous treatment with the alpha(2)-adrenergic receptor antagonists RX 821002 (40, 80 and 160 nmol/l mul) or yohimbine (160 and 320 nmol/l mul) abolished the inhibitory effect produced by icv injection of noradrenaline on pilocarpine-induced salivation in rats. Prazosin (alpha(1)-adrenergic receptor antagonist) injected icv did not change the effect of noradrenaline on pilocarpine-induced salivation. Prior icv injection of only RX 821002 (80 or 160 nmol/l mul) or yohimbine (320 nmol/l mul) increased pilocarpine-induced salivation. The results show that (1) contrary to its peripheral effects, noradrenaline acting centrally inhibits cholinergic-induced salivation in rats; (2) central mechanisms involving alpha(2)-adrenergic receptors inhibit pilocarpine-induced salivation. (C) 2002 Elsevier B.V. Ltd. All rights reserved.
Keywords: adrenergic receptors; cholinergic agonist; salivary secretion; parasympathetic; pilocarpine